Unveiling menarche: insights into the knowledge, attitudes, and practices of adolescent girls in Dhangadhi sub-metropolitan city - Joshi, Pragati; Shrestha, Tripti; Khatri, Manisha; Joshi, Prabhas; Bist, Amrit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Menarche refers to the onset of first menstruation. Despite being a normal, physiological process, menarche is still regarded as a taboo topic in some communities and ethnic groups. This situation makes many adolescent females vulnerable because of lack of knowledge, products, and infrastructure to deal with menarche. This study aims to assess the knowledge, attitude, and practices on menarche among adolescent girls in government schools of Dhangadhi sub-metropolitan city, a region where menstrual taboos are highly prevalent. Methods: A descriptive cross-sectional study was conducted among 383 adolescent school girls in Dhangadhi through a pre-tested semi structured questionnaire. Quantitative research method was applied through a self-administered questionnaire. Results: The study showed that the median age of menarche was 13 years. The main source of information about menarche was mother or grandmother (58.2%). Approximately, three fourth (71.4%) of the respondents had adequate knowledge, less than two third (61.6%) had positive attitude and nearly half (51.7%) of them had good practices on menarche. Factors like parents education and occupation, mother’s age, age at menarche, grade and family type were found to be significantly associated with knowledge, attitude and practices on menarche. Conclusions: Despite the fact that the majority of respondents had an adequate level of knowledge on menarche, the level of practices on menarche was still poor. This study highlights the need for policy makers to focus on implementing knowledge and awareness programs in government schools to educate students and their parents about menarche and menstrual hygiene.